Safety of IM Aripiprazole in Acute Agitation Associated with Dementia - Busse, Gregory (MD Conference Express, 2007)
Aripiprazole is an atypical antipsychotic approved for the treatment of schizophrenia. Agitation is a common symptom experienced by patients with dementia, and medications with a rapid onset of action and appropriate tolerability in the elderly are desirable in these situations. This article discusses a multicenter, double-blind, placebo-controlled pilot study to determine the tolerability of intramuscular aripiprazole in patients with acute agitation associated with dementia and to determine a maximum tolerated dose.